E-learning as a Modern Tool in the Shifting Landscape of Language Teaching - Laviniu Costinel LĂPĂDAT; Maria-Magdalena LĂPĂDAT (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
The landscape of language teaching has undergone a significant transformation in recent years with the emergence of e-learning. This modern tool has revolutionized the traditional approach to language teaching by providing new opportunities for learners to access language learning materials from anywhere in the world. E-learning has gained tremendous popularity due to its flexibility, accessibility, and cost-effectiveness. However, e-learning also poses several challenges, including the lack of face-to-face interaction, motivation and engagement, and technological barriers. To maximize the benefits of e-learning in language teaching, it is essential to address these challenges and ensure that learners have access to the necessary support and resources. This paper aims to explore the role of e-learning in the shifting landscape of language teaching by examining its benefits and challenges.